Suicide capability within the ideation-to-action framework: A systematic scoping review. - Luke T Bayliss; Steven Christensen; Andrea Lamont-Mills; Carol du Plessis (PLoS ONE)
Suicide capability is theorised to facilitate the movement from suicidal ideation to suicide attempt. Three types of contributors are posited to comprise suicide capability: acquired, dispositional, and practical. Despite suicide capability being critical in the movement from ideation-to-attempt, there has been no systematic synthesis of empirical evidence relating to suicide capability that would enable further development and refinement of the concept. This study sought to address this synthesis gap. A scoping review was conducted on suicide capability studies published January 2005 to January 2022. Eleven electronic databases and grey literature sources were searched returning 5,212 potential studies. After exclusion criteria application, 90 studies were included for final analysis. Results synthesis followed a textual narrative approach allocating studies based on contributors of suicide capability. Most studies focused on investigating only one factor within contributors. Painful and provocative events appear to contribute to acquired capability more so than fearlessness about death. Whilst emerging evidence for dispositional and practical contributors is promising, the small number of studies prevents further conclusions from being drawn. An unexpected additional cognitive contributor was identified. The focus of a single factor from most studies and the limited number of studies on contributors other than acquired capability limits the theoretical development and practical application of suicide capability knowledge. Given that suicide is a complex and multifaceted behaviour, future research that incorporates a combination of contributors is more likely to advance our understandings of suicide capability.